931 EVALUATION OF IATROGENIC ATRIAL SEPTAL DEFECT CLOSURE AFTER TEER. (15th December 2022) - Manni, Giulia; Macrini, Massimiliano; Idone, Gaetano; Lecis, Dalgisio; Marchei, Massimo; Di Landro, Alessio; Marsili, Giorgia; Illuminato, Federica; Galluccio, Chiara; Oro, Pietro; Minasi, Vincenzo; Muscoli, Saverio; et al.
Abstract: Iatrogenic atrial septal defect (iASD) represents one of the main access-related cardiac complications after trancatheter edge to edge (TEER) mitral valve repair with Mitraclip system. Transesophageal echocardiography (TEE) guiding supports a controlled and safe transseptal puncture. The rate of persistent iASD is 57, 50, and 25% after 1, 6, and 12 months post procedure. An elevated left atrial pressure after clip positioning correlates with iASD persistence. Its clinical impact is controversially discussed: Post-TEER iASD has been associated with right heart volume overload, as well as increased rates of heart failure (HF) hospitalization and death in some studies. In contrast, other studies have shown an association between post-TEER iASD and improved hemodynamics. In theory, creation of an iASD can decompress an overloaded left atrium, mitigating heart failure. Some studies have demonstrated that iASD closure can reduce significantly both right and left heart failure symptoms. We did a retrospective study enrolling in the period 2012-2022 twenty-one patients with severe mitral regurgitation treated with TEER. Our aim was to evaluate the clinical outcomes (symptoms, signs of heart failure, NYHA functional class) and echocardiographic parameters (PAPs, TAPSE, Right Atrium Area) in two group of patients: Group A underwent iASD closure during the TEER and Group B after one month following the TEER. At 1-month follow-up all patients with repaired mitral regurgitation showed an improvement in the NYHA class (from IV-III to II-I) and no need for re-hospitalization with no significant differences between two groups. In the Group A there were two adverse events during the recovery (2 major bleeding); while there were no adverse events in patients undergoing iASD closure after wise. There was 1 death in the first month after the procedure in group A, while there wasn't any in group B. Statistical analysis showed no significant differences in terms of NYHA class improvement in the two groups (p=0.91). We observed a greater reduction in PAPs in patients going to encounter intraprocedural DIA closure which was found to be statistically significant (p=0.01). Regarding TAPSE, there was a difference in terms of improvement which was found to be greater in the group A. However, this finding was not found to be statistically significant. We also assessed the right atrium area: in group A, we registered a mean preprocedural value of 28 cmq and a postprocedural value of 34 cmq; in group B the values were 20 cmq and 24 cmq, respectively, with a nonstatistically significant difference in terms of atrial enlargement post device placement. In conclusion, we can assume that the improvements in symptomatology are not closely related to iASD closure. However, it must considered that patients in group A had more unfavorable echocardiographic values before the procedure than those in group B, and probably, if we had not closed the iASD immediately during the procedure, these patients would have had worse symptomatology. Therefore, targeted patient selection is essential.